Template-assisted growth of highly oriented 3D graphene pH sensor towards new avenues for biosensor - Perumal, V. (Institute of Electrical and Electronics Engineers Inc., 2017)
In recent times, the high flexibility and exceptional electrical conductivity of free-standing monolithic 3D graphene has attracted considerable attention in the field of electronic sensor development for real time sensing. In this work, we have synthesized free-standing monolithic 3D graphene through chemical vapor deposition (CVD) using nickel foam as a sacrificial template for pH sensing. The surface and structural morphology were characterized by scanning electron microscopy and Raman spectroscopy. The results show a highly oriented and defect free monolithic 3D graphene which imitates the nickel template surface and the 3D graphene microporous structure firmly retained its structure even after Ni template etching. The voltage versus current and resistance corresponding to pH (pH-4 to pH-10) at constant current of 1μA are detailed in delineated graphs. It shows a linear regression of R = (211.90 -13.67pH) and a measured sensitivity of 13.67 Ω/pH for the developed 3D graphene device. The synthesized 3D graphene paves a way for the development of highly sensitive, selective and flexible sensing platform which presents a new avenue for biosensor development. © 2017 IEEE.